2018
DOI: 10.1002/pat.4299
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis study of the thermo‐sensitive copolymer carrier of penicillin G acylase

Abstract: Reversible‐addition‐fragmentation chain transfer polymerization method was adopted here in this study to prepare a series of thermo‐sensitive tri‐block copolymer carrier, poly(N,N‐diethylacrylamide‐b‐β‐hydroxyethyl methacrylate‐b‐glycidyl methacrylate), PDEA‐b‐PHEMA‐b‐PGMA (named as DHG). Their structures and temperature sensitivity performances were further characterized by the nuclear magnetic resonance, the gel permeation chromatography, and the fluorescence spectroscopy, respectively. It has been identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…These involve heating of the mold material itself by Joule or induction heating . Other methods employ external heating of the mold surface, such as infrared heating or steam heating . Laser‐heating of the mold has also been used to achieve extremely rapid mold heating on the order of 300 °C per second, although with a spatially inhomogeneous temperature profile over a small area.…”
Section: Injection Moldingmentioning
confidence: 99%
“…These involve heating of the mold material itself by Joule or induction heating . Other methods employ external heating of the mold surface, such as infrared heating or steam heating . Laser‐heating of the mold has also been used to achieve extremely rapid mold heating on the order of 300 °C per second, although with a spatially inhomogeneous temperature profile over a small area.…”
Section: Injection Moldingmentioning
confidence: 99%
“…It can be summed up as when the target density is too large because there are more types and quantities of functional groups available for reaction on the PGA; as a result, a PGA can be immobilized by multiple targets, which will cause the conformation of the PGA active center to be deformed, so the activity is lowered. However, combining the research work of our laboratory on immobilized PGA, in addition to the above inference, here is a new conjecture: The mutual extrusion may lead to distortion of the conformation of the PGA activity center under stress, which leads to a decrease in enzyme activity recovery due to more deformable active center conformation. Based on the above hypothesis, our lab designed and synthesized a disordered block temperature‐sensitive polymer (PDEA‐b‐PHEMA‐b‐P (MMA‐co‐GMA)) as the carrier of PGA, with MMA as the co‐monomer of target GMA, and investigated the influence of target distance on the activity recovery rate of immobilized PGA and obtained that the activity recovery rate increased with the increase of target spacing, and when the molar ratio of MMA to GMA in the copolymer was about 8.75:1, the recovery of activity of immobilized PGA could be up to 63.50%, which was 21.70% higher than that of pure GMA .…”
Section: Immobilization Pgamentioning
confidence: 78%
“…Now, LCST polymer has been applied to biomedical, catalytic, sensor, immobilized enzymes, and other fields. In the field of immobilized enzymes, Ke Li et al synthesized the tri‐block temperature‐sensitive polymer PDEA‐b‐PHEMA‐b‐PGMA and applied it to the PGA immobilization carrier for the first time, successfully using the polymer sol state realize the immobilization of the PGA and the catalytic conversion of the immobilized PGA, which effectively increased the mass transfer rate, and the recovery of the immobilized PGA in the gel state (Figure ). However, the results showed that although the carrier type increased the immobilized PGA mass transfer rate, its recovery performance was still lower than that of magnetic nanocarriers.…”
Section: Immobilization Pgamentioning
confidence: 99%
“…24,25 Without special intermolecular interactions in a hybrid system, common surface modifications must improve compatibility by enhancing van der Waals interaction (vdW interaction) between the polymeric matrix and fillers. [26][27][28] It is reported that the vdW interaction is considered as a weak interaction of around 0.4-4 kJ mol −1 while the π-π stacking interaction is approximately 10-100 times stronger than that of the vdW interaction. 29 Thus, we can design a polymeric matrix containing conjugated aromatic structures to interact with graphite without complex modification of the graphite, which would preserve the TC of graphite as well as reducing interfacial thermal resistance.…”
Section: Introductionmentioning
confidence: 99%